Anthelmintic activity of the flowers of Sesbania grandiflora Pers. - P.L. Rajagopal; K, Premaletha; K. R. Sreejith, (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2016)
In present study acetone, ethanol and aqueous extracts of the flowers of Sesbania grandiflora were investigated for their anthelmintic activity against Pheretima posthuma. Three concentrations (100, 150, 200 mg/ml) of each extract were studied. This study is mainly concerned with the determination of time of paralysis and time of death of the worms. When there was a gradual increase in the dose, a gradual increase in the anthelmintic activity was observed. The ethanolic extract of the flower showed a significant anthelmintic activity at highest concentration of 200 mg/ml.